A bildung e a formação do leitor literário: sugestões de aplicabilidade de textos literários - RODRIGUES, Marco Aurélio Godinho (2024)
The present research aims to investigate and propose suggestions for activities for the training of literary readers in high school through the notion of Bildung. When we approach Bildung, the formation of the literary reader, its representations, and literary literacy, we realize the need to know the particularities implicit in the ideas discussed here, going beyond the prior knowledge of teachers and students in how they transmit and learn. The formation of the reader's critical consciousness with an emphasis on literary reading results in the work of teachers at school using Portuguese language and Brazilian literature textbooks, which feature literary texts of different genres in their sections. This makes the work of literary reading practices in literature classes fundamentals, especially literary literacy. The methodology included a bibliographical design, of a qualitative and explanatory nature. For this, the investigation is based on the reading of Weber (2011), Hermann (2010), Dalbosco (2009), Cosson (2004, 2006, 2009, 2014, 2018, 2021), Klafki (2007), Gadamer (2004), Paulino (20010), Colomer (2003), Soares (2002, 1999), Kleiman (1995) and others. In this scenario, we sought to understand the various skills and competencies of the representations listed here to contribute to bildung as a process of training literary readers in high school and literary literacy.